2015
DOI: 10.1007/s10753-015-0268-0
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin Pretreatment Attenuates Seawater Aspiration-Induced Acute Lung Injury in Rats

Abstract: Seawater drowning-induced acute lung injury (ALI) is a serious clinical condition characterized by increased alveolar-capillary permeability, excessive inflammatory responses, and refractory hypoxemia. However, current therapeutic options are largely supportive; thus, it is of great interest to search for alternative agents to treat seawater aspiration-induced ALI. Erythropoietin (EPO) is a multifunctional agent with antiinflammatory, antioxidative, and antiapoptotic properties. However, the effects of EPO on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…[29] Moreover, Ji et al showed that rhEPO pretreatment inhibited NF-κB p65 and the release of proinflammatory cytokines. [14] Likewise, attenuation of cytokines was observed with rhEPO pretreatment in meconium-instilled rats in our study. Pulmonary inflammation is a key feature in the pathogenesis of MAS; therefore, the significant attenuation of inflammation with rhEPO pretreatment observed in this study may suggest the potential for use of EPO as a therapeutic agent in the prevention of lung damage from MAS.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…[29] Moreover, Ji et al showed that rhEPO pretreatment inhibited NF-κB p65 and the release of proinflammatory cytokines. [14] Likewise, attenuation of cytokines was observed with rhEPO pretreatment in meconium-instilled rats in our study. Pulmonary inflammation is a key feature in the pathogenesis of MAS; therefore, the significant attenuation of inflammation with rhEPO pretreatment observed in this study may suggest the potential for use of EPO as a therapeutic agent in the prevention of lung damage from MAS.…”
Section: Discussionsupporting
confidence: 79%
“…[5] A growing body of evidence suggests that the protective role and potent anti-inflammatory activity of EPO, including inhibition of leukocyte infiltration and reduced levels of proinflammatory cytokines, has been reported in various in vivo studies. [3,[14][15][16][17][18][19] Ozer et al [21] showed that treatment of hyperoxia-exposed newborn rat pups with rhEPO significantly improved alveolar structure, and lessened fibrosis. Lee et al [3] also showed that rhEPO treatment significantly improved hyperoxia-induced lung damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The marine industry has been developing in recent years, and marine workers are prone to various open injuries [26]. Several previous studies have reported that SW immersion causes large amounts of inflammatory factors, such as IL-8, TNF, and NO, to be released from the injured area, causing multiple organ damage in the body and increasing the probability of disseminated intravascular coagulation, which ultimately leads to an increase in mortality [4,[27][28][29][30][31]. However, the effects of SW immersion on wound repair of full-thickness skin defects and its mechanism have not been reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Because pulmonary surfactant‐associated protein levels can be elevated in tissue specimens, not only in drowned victims but also in cases of acute lung injury (ALI) and acute respiratory distress syndrome (ARDS), pulmonary surfactant protein A (SP‐A) can be useful as a marker of asphyxiation and ALI . ARDS/ALI is characterized by pulmonary edema and severe refractory hypoxemia, including drowning and asphyxia (hanging, suffocation, and aspiration) . Funayama et al and Zhu et al reported use of SP‐A immunohistochemical (IHC) staining in forensic pathology, as the IHC distribution of SP‐A is stable during decomposition.…”
mentioning
confidence: 99%